A comparison of national seasonal influenza treatment guidelines across the Asia Pacific region. - Ellen Beer; Simon Boyd; Phrutsamon Wongnak; Thundon Ngamprasertchai; Nicholas J White (PLOS Global Public Health)
Seasonal influenza leads to 2-3 million infections and up to 650,000 global deaths annually, with particularly high mortality in Asia and relatively low annual vaccination rates for prevention. Relatively lower attention is paid to antiviral treatment as a facet of influenza response strategy both in research and national policy. This study compares national influenza treatment guidelines across countries in the Asia Pacific region, and assesses the antiviral recommendations, comprehensiveness, availability, and quality, compared with World Health Organisation (WHO) guidelines. Ministry of Health websites were searched, and key stakeholders were contacted to obtain national influenza treatment guidelines. Official guidelines detailing pharmacologic treatment for seasonal influenza were included. Key data for comparison were extracted and quality appraisal was conducted using the AGREE II instrument. Out of 49 countries and areas in the World Health Organisation Western Pacific and South-East Asia regions, under half (14/49; 28.6%) had established national influenza treatment guidelines. Nine (9/49; 18.4%) reported no seasonal flu guidelines at all, and information could not be obtained for 25 (51.0%). All guidelines recommend oseltamivir in line with WHO recommendations, although rationale and evidence reviews were often missing. There was variation in recommendations for other antivirals, indications for treatment, definitions of severity and recency of publication. The AGREE II tool quality assessments revealed the highest average scores were observed in the 'presentation' domain and lowest scores in 'editorial independence' and 'rigour of development' domains, demonstrating limited evidence-based guideline development. The variability in recommendations and definitions highlight the need for a stronger evidence base with direct comparisons of antiviral treatment for hard and soft endpoints, and improvements in systematic guideline development. Established treatment guidelines are a key component of national influenza response strategy and in the post-covid pandemic era, renewed attention to seasonal influenza management is surely warranted.